2023
DOI: 10.2298/pan190531004s
|View full text |Cite
|
Sign up to set email alerts
|

Why the increase in the retirement age will lead to more inequality and poverty? An ignored fairness problem

Abstract: In this study, we show with the help of a simple model that an increase of the retirement age has a negative impact on the distribution of pension benefits in the Bismarckian as well in the Beveridgean pension system. In both systems, the distribution of pension benefits will change in favour of high-income earners. Additionally, we show that the increasing gap in the life expectancies of low and high-income earners will increase inequality. Both results are a consequence of the positive rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Lin and Lin (2016) inferred from the prediction results of the option value model that, irrespective of male workers, female workers or low-income labor groups, delayed retirement will have a certain degree of negative impact [31]. By using an overlapping generations model, Stauvermann and Hu (2018) analyzed the economic impacts resulting from an increase in life expectancy and an increased retirement age on the pension system. The results showed that the share of capital income had a crucial effect on pension revenue [32].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin and Lin (2016) inferred from the prediction results of the option value model that, irrespective of male workers, female workers or low-income labor groups, delayed retirement will have a certain degree of negative impact [31]. By using an overlapping generations model, Stauvermann and Hu (2018) analyzed the economic impacts resulting from an increase in life expectancy and an increased retirement age on the pension system. The results showed that the share of capital income had a crucial effect on pension revenue [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…By using an overlapping generations model, Stauvermann and Hu (2018) analyzed the economic impacts resulting from an increase in life expectancy and an increased retirement age on the pension system. The results showed that the share of capital income had a crucial effect on pension revenue [32]. Romm and Wolny (2012) found that delayed retirement policy will reduce individual and aggregate savings rates and will even lead to a decline in output [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, recent research by Stauvermann et al (2023) [18] reveal that the Bismarckian system, in fact, exhibits a regressive impact. This occurs because in many developed countries, high-income individuals tend to have significantly higher life expectancies than low-income individuals.…”
Section: Introductionmentioning
confidence: 97%